Revision of the shore-fly genus Peltopsilopa Hendel (Diptera: Ephydridae) - Savaris, Marcoandre; Marinoni, Luciane; Mathis, Wayne N. (Zootaxa, 2016)
The Neotropical shore-fly genus Peltopsilopa Hendel is revised and now includes three species: P. acuta n.sp.; P. anisotomoides (Karsch), new combination; and P. schwarzi Cresson. A fourth species name, P. aspistes Hendel, is recognized as a junior synonym of P. anisotomoides (Karsch). We confirm that Peltopsilopa is closely related to Cressonomyia Arnaud and that the genus is in the tribe Psilopini, subfamily Discomyzinae. We provide a revised generic diagnosis and key to South American genera of Psilopini to facilitate identification of Peltopsilopa. The included species descriptions are extensively documented with illustrations, photographs, and distribution map.